Optimal temperature for the long-term culture of adult porcine islets for xenotransplantation - Sakata, Naoaki; Yoshimatsu, Gumpei; Kawakami, Ryo; Aoyagi, Chikao; Kodama, Shohta (Frontiers in Immunology, 2023)
Porcine islet xenotransplantation represents a promising therapy for severe diabetes mellitus. Long-term culture of porcine islets is a crucial challenge to permit the on-demand provision of islets. We aimed to identify the optimal temperature for the long-term culture of adult porcine islets for xenotransplantation. We evaluated the factors potentially influencing successful 28-day culture of islets at 24°C and 37°C, and found that culture at 37°C contributed to the stability of the morphology of the islets, the proliferation of islet cells, and the recovery of endocrine function, indicated by the expression of genes involved in pancreatic development, hormone production, and glucose-stimulated insulin secretion. These advantages may be provided by islet-derived CD146-positive stellate cells. The efficacy of xenotransplantation using islets cultured for a long time at 37°C was similar to that of overnight-cultured islets. In conclusion, 37°C might be a suitable temperature for the long-term culture of porcine islets, but further modifications will be required for successful xenotransplantation in a clinical setting.